Manajemen Pembangunan Ekonomi Lokal Berbasis Daya Saing (Studi Kasus pada Kabupaten Teluk Bintuni, Papua Barat) - Candra Fajri Ananda (Jurnal Aplikasi Manajemen, 2010)
Significant development problems in West Papua province, e.g., Bintuni District are low regional competitiveness comparing to other districts in Indonesia in general. In fact, Bintuni District is a region with high potential natural resources, although poverty, unemployment and low economic growth contribute to high challenges of regional development. Therefore, different research objectives are stated such as analyzing on regional competitiveness and formulating local economic development based on potential competitiveness. Cluster analysis is implemented to explore the stated problems in Kaimana district, Raja Ampat, Teluk Bintuni, Sorong Selatan, Teluk Wondana, Fak Fak and Manokwari district, Sorong district and Sorong municipality. The research results show that regional competitiveness is still low comparing to other regions in West Papua province. The regional development strategy should concern on local economic development through encouraging of SME’s and improving linkages between sectors.Keywords: Competitiveness, local economic development, cluster analyzis